Adhesion molecule interactions facilitate human immunodeficiency virus type 1-induced virological synapse formation between T cells. - Jolly, C; Mitar, I; Sattentau, Q (2007)
Human immunodeficiency virus type 1 (HIV-1) can spread between CD4+ T cells by using a virological synapse (VS). The VS assembly is a cytoskeleton-driven process dependent on HIV-1 envelope glycoprotein (Env)-receptor engagement and is hypothesized to require adhesion molecule interactions. Here we demonstrate that leukocyte function-associated antigen 1 (LFA-1), intercellular adhesion molecule 1 (ICAM-1), and ICAM-3 are enriched at the VS and that inhibition of these interactions influences conjugate formation and reduces VS assembly. Moreover, CD4+ T cells deficient in LFA-1 or with modified LFA-1 function were less able to support VS assembly and cell-cell transfer of HIV-1. Thus, cognate adhesion molecule interactions at the VS are important for HIV-1 spread between T cells.